2020
DOI: 10.3390/app10134487
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma (PRP) in Dental Extraction of Patients at Risk of Bisphosphonate-Related Osteonecrosis of the Jaws: A Two-Year Longitudinal Study

Abstract: Dental extraction has often been described as the main trigger event of osteonecrosis of the jaws (ONJ). This longitudinal hospital-based study aimed to evaluate the outcome at 2 years of a standardized medical-surgical protocol for dental extraction, combined with platelet rich-plasma (PRP) application, compared with conventional protocol not combined with PRP or any other autologous platelet concentrate in cancer (ONC) and osteometabolic (OST) patients, at risk of bisphosphonate (BP)-related ONJ. Twenty pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…6,8,14 The platelet-rich plasma (PRP) has been suggested as an integral modality to prevent AO, while the antibiotic prescription is not an ideal strategy to treat or prevent AO after dental extractions. 21,22 In our study, 61 cases (57.0%) of AO were observed in tooth extractions performed by dental interns, while 46 cases (43.0%) were found in extractions performed by qualified dentists or specialists. These results align with Puidokas et al's study, 20 which reported that the initial absence of a clot or its mechanical elimination (traumatic tooth extractions) or altered formation and the longer healing period are major causes of dry socket.…”
Section: Discussionmentioning
confidence: 46%
“…6,8,14 The platelet-rich plasma (PRP) has been suggested as an integral modality to prevent AO, while the antibiotic prescription is not an ideal strategy to treat or prevent AO after dental extractions. 21,22 In our study, 61 cases (57.0%) of AO were observed in tooth extractions performed by dental interns, while 46 cases (43.0%) were found in extractions performed by qualified dentists or specialists. These results align with Puidokas et al's study, 20 which reported that the initial absence of a clot or its mechanical elimination (traumatic tooth extractions) or altered formation and the longer healing period are major causes of dry socket.…”
Section: Discussionmentioning
confidence: 46%
“…Mauceri et al [ 70 ] aimed to evaluate the use of PRP in post-extraction sockets in patients with cancer and osteometabolic patients at risk of BRONJ (bisphosphonate-related osteonecrosis of the jaw). The study’s outcomes revealed that two years after extraction and treatment with PRP, no patient had clinical or radiological signs of osteonecrosis of the jaw.…”
Section: Resultsmentioning
confidence: 99%
“…When conservative treatment cannot result in cure or improvement, surgical intervention for removal of the bone is necessary. Due to the ability of PRP to increase tissue vascularisation and release multiple growth factors, the use of PRP has been suggested by many authors to enhance postsurgical wound healing [ 70 , 71 ]. PRP releases a wide variety of key biological mediators that are important during tissue repair [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, platelet-rich plasma (PRP) and platelet-rich fibrin (PRF), which are autogenous sources of many growth factors, including platelet-derived growth factor (PDGF), transforming growth factor-beta (TGF-β), epidermal growth factors (EGF) and vascular endothelial growth factors (VEGF), have often been used in the regeneration of extraction sockets [ 42 ]. For instance, Mauceri et al has evaluated the effect of PRP on reducing the risk of MRONJ for patients receiving antiresorptive drugs, and concluded that PRP application may contribute to a reduction in the occurrence of MRONJ [ 43 ]. Kailas et al reported that PRP enhanced the osteogenic response in initial bone healing, although there was no beneficial effect at the late wound healing period in extraction sockets [ 44 ].…”
Section: Discussionmentioning
confidence: 99%